Pengaruh SEFT (Spiritual Emotional Freedom Technique) Terhadap Penurunan Tekanan Darah Lansia Hipertensi: Literature review - Suhanda, Suhanda; Fitriani, Ade; Permatasari, Wulan (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2021)
Elderly is a process of aging with increasing age of the individual characterized by with decreased function of organs such as the brain, heart, liver and kidneys and increased tissue loss. One of the system disorders that are often experienced by the elderly is the cardiovascular system such as hypertension. Hypertension or high blood pressure is one of the global health problems that requires special attention today. Hypertension can be fatal if not properly controlled or commonly referred to as complications. Complications of hypertension occur due to organ damage caused by a very high increase in blood pressure for a long time. This situation can be overcome by providing SEFT therapy actions, the purpose of this literature review is to review articles related to SEFT Therapy. Where in the discussion of the Decrease in Blood Pressure of Hypertensive Elderly, the method used in writing this literature review is by searching sourced from electronic data hase includes Google Scholar from 2015-2020 using 15 journals related to SEFT Therapy management. The results of the literature review indicate that there is a relationship between SEFT Therapy and a decrease in blood pressure in hypertensive elderly.